2007
DOI: 10.1038/nm1555
|View full text |Cite
|
Sign up to set email alerts
|

Ccr2 deficiency impairs microglial accumulation and accelerates progression of Alzheimer-like disease

Abstract: Microglia are the principal immune cells of the brain. In Alzheimer disease, these brain mononuclear phagocytes are recruited from the blood and accumulate in senile plaques. However, the role of microglia in Alzheimer disease has not been resolved. Microglia may be neuroprotective by phagocytosing amyloid-beta (Abeta), but their activation and the secretion of neurotoxins may also cause neurodegeneration. Ccr2 is a chemokine receptor expressed on microglia, which mediates the accumulation of mononuclear phago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
683
4
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 792 publications
(716 citation statements)
references
References 48 publications
26
683
4
3
Order By: Relevance
“…Blood-borne monocytes have been shown to infiltrate damaged or diseased brain tissue in animal models of other human neurological disease, such as the EAE model of multiple sclerosis (35), Alzheimer's disease (27,28,44), and traumatic brain injury (13,45). Previous studies have also reported elevated numbers of peripheral immune leukocytes after epileptiform activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood-borne monocytes have been shown to infiltrate damaged or diseased brain tissue in animal models of other human neurological disease, such as the EAE model of multiple sclerosis (35), Alzheimer's disease (27,28,44), and traumatic brain injury (13,45). Previous studies have also reported elevated numbers of peripheral immune leukocytes after epileptiform activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…A subclass of circulating monocytes expresses high levels of CCR2 (25), whereas microglia lack CCR2 expression (11). Notably, Ccr2 knockout mice display reduced recruitment of circulating monocytes into inflamed tissues, including the brain, in injury and disease animal models, such as traumatic brain injury (13,26), EAE models (14,15), and Alzheimer's disease (27,28).…”
mentioning
confidence: 99%
“…In addition to resident microglia, mononuclear cells that are recruited from the blood are key players in AD pathogenesis; in fact, depletion of this cell pool or ablation of the receptor protein that recruits monocytes into the brain, accelerated Ab accumulation and animal mortality ( [68,212]). On the other hand, anti-inflammatory agents such as COX-1 inhibitors induced a dose-dependent reduction in pathology in humans and transgenic mouse model of AD [154].…”
Section: Animal Models Of Alzheimer's Diseasementioning
confidence: 99%
“…Purinergic signaling has been shown to influence the initiation, progression, and downregulation of an inflammatory response [210], and the P2Y 2 R is an important mediator of neuroinflammation [15]. As described above, IL-1β regulates the expression of the P2Y 2 R in neurons [48] and other proinflammatory mediators in the AD brain [134,211], and overexpression of IL-1β has been associated with head trauma, epilepsy, genetic polymorphisms, and age-related damage [212,213]. In AD, IL-1β increases with Aβ plaque accumulation and dystrophic neurite formation [200].…”
Section: P2y 2 Rs In Cns Inflammationmentioning
confidence: 96%
“…Injury or other disturbances to the CNS trigger rapid transformation of ramified (quiescent) microglia into activated phenotypes that further develop into phagocytic macrophages [129,130]. Activated microglia can be either neuroprotective [130][131][132][133][134] or neurotoxic [131,[135][136][137]. Although the CNS is considered to be an immune-privileged site because the BBB limits entry of blood-borne cells and proteins, recent findings indicate that peripheral leukocytes have important physiological and pathophysiological functions in the CNS [138].…”
Section: P2y 2 Receptors In Glial Cellsmentioning
confidence: 99%